Heavy Metal Contamination of Foods by Refuse Dump Sites in Awka, Southeastern Nigeria - J. K. C. Nduka; O. E. Orisakwe; L. O. Ezenweke; M. N. Chendo; T. E. Ezenwa (The Scientific World Journal)
The impact of heavy metals from refuse dumps on soil, food, and water qualities in Awka, Nigeria was studied. Soil samples (top and 1.35 m deep) were collected from five refuse dumps digested with conc. HNO3 and HClO4. The heavy metals (lead, manganese, arsenic, chromium, cadmium, and nickel) in vegetables (spinach, fluted pumpkin), root crop (cocoyam), and surface and ground water were determined using an atomic absorption spectrophotometer (AAS). Chemical properties of the soil and bacteria were determined. Heavy metals were found to be more concentrated at a depth of 1.35 m. Manganese was high in shallow wells and borehole water samples with the highest levels as 0.538 and 0.325 mg/l, respectively. Nickel levels in the borehole sample ranged from 0.001 to 0.227 mg/l, whereas the highest level of lead was 0.01 mg/l. The Obibia stream had the highest levels of manganese and lead. Linear regression analyses showed that the relationship between soil heavy metals and farm produce heavy metals was strong. Taken together, we may conclude that the consumption of leafy vegetables and crops produced on contaminated soils may pose a health risk to those that reside around the refuse dumps.